Disturbed glucose metabolism and left ventricular geometry in the general population – results from the Gutenberg health study. (25th November 2020) - Schmitt, V.H; Remmert, A.-M; Toebs, S.-O; Schulz, A; Leuschner, A; Arnold, N; Koeck, T; Panova-Noeva, M; Beutel, M; Pfeiffer, N; Strauch, K; Lackner, K.J; et al.
Abstract: Background: Prediabetes and type 2 diabetes mellitus (T2DM) have been demonstrated to alter left ventricular geometry and promote left ventricular (LV) hypertrophy (LVH). However, the impact of impaired glucose metabolism on cardiac structure is still not completely understood and controversially discussed. Purpose: To investigate the impact of prediabetes and T2DM on left ventricular geometry and their potential interaction with LVH in the prediction of survival. Methods: Data from the Gutenberg Health Study (N=15, 010) – a population-based study with highly standardized phenotyping – were analysed. Information was obtained from computer-assisted personal interviews, medical-technical examinations, laboratory measurements in fasting state and echocardiography according to standard operating procedures with detailed quality control. Individuals with other types of diabetes or hyperinsulinemia were excluded from analysis. Study participants aged 35 to 74 years were categorized according to long-term glucose state (HbA1c) into euglycemia, prediabetes and T2DM. LV geometry was assessed according to current guideline recommendations. Multivariable regression analyses were performed to evaluate the association between glucose state and measures of left ventricular geometry. Survival analyses were carried out to assess the prognostic impact dependent on the presence of LVH. Results: The analysis sample comprised 14, 852 individuals aged 55.0±11.1 years (49.5% females). The prevalence of LVH was 10.2% (n=1, 227) in euglycaemia, 17.2% in prediabetes and 23.8% in T2DM. Similarly, concentric and eccentric hypertrophy had the highest prevalence in T2DM (13.1% and 10.8%, respectively), followed by prediabetes (9.6% and 8.2%) and euglycaemia (5.7% and 4.5%). In multivariable regression analysis with adjustment for age, sex, traditional cardiovascular risk factors (CVRF), C-reactive protein and LV function, T2DM had a higher impact on relative wall thickness (β: 0.0135 [0.0087; 0.0182]; P<0.0001) and LV mass (β: 5.46 [4.89; 6.03]; P<0.0001) than prediabetes (β-estimaterelative wall thickness 0.00145 [−0.0031; 0.006]; P=0.53; β-estimateLV mass 2.73 [2.19; 3.28]; P<0.0001) compared to euglycemia. During a median follow-up of 9.0 [interquartile range 7.7; 10.4] years, prediabetes did not predict all-cause mortality independent of age, sex and CVRF in Cox regression analysis in individuals without LVH (hazard ratio (HR) 1.15 [0.90; 1.46]; P=0.27) or those with LVH (HR 1.46 [0.97; 2.18]; P=0.069). In comparison, T2DM was a strong and independent predictor of mortality both in absence (HR 1.59 [1.29; 1.96]; P<0.0001) and presence of LVH (HR 2.67 [1.94; 3.66]; P<0.0001). Conclusions: Although cardiac geometry is altered both in presence of prediabetes and T2DM, only T2DM is a strong predictor of premature mortality in the general population. This merits consideration for future preventive strategies to decrease the burden of cardiovascular disease. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): The study was supported by the Federal Ministry of Education and Research (BMBF), the government of Rheinland-Pfalz and the Center for Translational Vascular Biology (CTVB) of the Johannes Gutenberg-University of Mainz, Germany.